خصوصية التعويض في شكاوى عدم الانتهاك في قانون منظمة التجارة العالمية - صلاح الدين, بوجلال (Sciences humaines, 2014)
يعد التعويض أحد المعالم الأساسية وفقا للقواعد العامة للمسؤولية الدولية كوسيلة لجبر الضرر، غير أنه في قانون منظمة التجارة العالمية يتميز بخصوصية تجعله مختلفا كثيرا عن مفهومه التقليدي. ودراستنا هذه تحاول إماطة اللثام عن مفهوم التعويض في دعاوى عدم الانتهاك مثلما تم إدراجها في التفاهم الخاص بتسوية المنازعات في ظل قانون منظمة التجارة العالمية، كاشفة عن خصوصية هذا النظام، إنطلاقا من النصوص ذات الصلة ومختلف القضايا التي عرضت بهذا الصدد أمام جهاز تسوية المنازعات، ومحاولة العناية بتقييمه مع مراعاة طبيعة النظام التجاري الدولي.    Compensation is one of the key features in accordance with the general rules of international responsibility as a means of reparation, but that in the WTO law is characterized by specificity to make it much different from the traditional concept. And this study is trying to uncover the concept of compensation in situations of non-violation, as was inserted in the Dispute Settlement Understanding under WTO law, revealing the specificity of this system, from the relevant texts and the various cases presented in this regard before the DSB, and try to care evaluated  taking into account the nature of the international trading system.